Association between time perspective and metacognition among Lebanese adults: the mediating role of mindfulness - Abdallah Chahine; Christian-Joseph El Zouki; Mariam Mhanna; Souheil Hallit; Sahar Obeid (BMC Psychiatry, 2023)
Abstract Background Mindfulness may serve as a component of metacognitive beliefs and can also be viewed as a form of time perspective. The interplay between time perspective and metacognitive beliefs remains understudied. Both aspects, however, display considerable stability over time and significantly influence an individual’s life and well-being. Lebanon, marked by its diverse and complex history, struggles with various political, social, and economic challenges. This study offers a valuable and unprecedented opportunity to examine these connections within a distinct cultural context, shedding light on the unique experiences of the Lebanese population. Therefore, our research aims to investigate the connection between time perspective and metacognition, with a focus on the role of mindfulness as a mediator. Methods This cross-sectional study was conducted from August to November 2022 and involved participants from various regions of Lebanon. The questionnaire included sociodemographic data and scales such as the Arabic versions of the 15-item Short Form of the Zimbardo Time Perspective Inventory, the Metacognitions Questionnaire, the Freiburg Mindfulness Inventory and the Acceptance and Action Questionnaire (AAQ-2). Results Our investigation recruited 423 participants. The analysis showed that individuals with a positive stance on their past, a hedonistic present, or a future-oriented outlook exhibited heightened levels of mindfulness. This elevated state of mindfulness, in turn, demonstrated a significant link to augmented cognitive self-consciousness (An increased introspection into one’s own thoughts). We also observed a direct association between a future-focused time perspective and high scores of cognitive self-consciousness. Furthermore, mindfulness emerged as a crucial mediator in the relationships between time perspectives and negative beliefs about the danger of worry. Similarly, individuals with a positive view on their past, a hedonistic present orientation, or a future-focused mindset demonstrated elevated levels of mindfulness, which was correlated with less negative beliefs about the danger of worry. Notably, a positive past perspective was directly associated with less negative views on worry and the subsequent loss of control, whereas higher future focused time perspective scores was significantly and directly associated with more negative beliefs about worry, whereas more future focused time perspective was significantly and directly associated with more negative beliefs about worry. Conclusion Our findings found several meaningful associations between our variables, but it primarily underscored the significance of considering distinct subcomponents within mindfulness and psychopathological metacognition that may overlap, shedding light on their differential impacts on psychological well-being. We were also able to mirror the dual pathway theory of time perspective suggested in previous studies. These insights carry notable implications for the development and refinement of mindfulness-based and metacognitive interventions, emphasizing the need for tailored approaches that consider varying time perspectives. Continued investigation in this area promises to advance our understanding of these constructs and refine their practical applications in mental health interventions and well-being enhancement strategies.